Unique Blood Pressure Characteristics in Mother and Offspring After Early Onset Preeclampsia - Lazdam, Merzaka; de la Horra, Arancha; Diesch, Jonathan; Kenworthy, Yvonne; Davis, Esther; Lewandowski, Adam J.; Szmigielski, Cezary; Shore, Angela; Mackillop, Lucy; Kharbanda, Rajesh; Alp, Nicholas; Redman, Christopher; et al. (Hypertension (Dallas, Tex. 1979), 2012)
Risk of hypertension in mother and offspring after preeclampsia is greater if preeclampsia develops early in pregnancy. We investigated whether those who develop early onset disease have unique adverse blood pressure characteristics. One hundred forty women were studied 6 to 13 years either after a pregnancy complicated by preeclampsia (45 women with early onset preeclampsia before 34 weeks gestation and 45 women with late-onset preeclampsia) or after a normotensive pregnancy (50 women). Forty-seven offspring from these pregnancies also participated. Data on maternal antenatal and postnatal blood pressures were extracted from maternity records and related to peripheral, central, and ambulatory blood pressure measurements in later life. Compared with late-onset preeclampsia, early onset preeclampsia was associated with higher diastolic blood pressure 6 weeks postnatally (86.25±13.46 versus 75.00±5.00 mm Hg, P<0.05), a greater increase in blood pressure relative to booking blood pressure over the subsequent 6 to 13 years, and higher nocturnal systolic and diastolic blood pressures in later life (111.07±13.18 versus 101.13±11.50 mm Hg, P=0.04, and 67.00±7.25 versus 58.60±5.79 mm Hg, P=0.002). Furthermore, at age 6 to 13 years their offspring had higher systolic blood pressure compared with those born to late-onset preeclampsia (96.27±7.30 versus 88.39±7.57 mm Hg, P=0.005). Mothers who developed early onset preeclampsia, and the offspring of that pregnancy display specific adverse blood pressure characteristics later in life. These are not evident in mothers and offspring after late-onset preeclampsia or normotensive pregnancy.